A Journalism Teaching Model Focused on Interpersonal Intelligence in News Writing for Students at the University of Muhammadiyah North Sumatra - Halimah Tussa’diah; Dewi Juni Artha; Dian Novianti Sitompul; Melyani Sari Sitepu (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study was prompted by the fact that students’ news writing skills are not yet up to standard, as evidenced by their difficulties in identifying ideas, structuring news articles and using journalistic language, as well as a lack of interaction during lessons. In fact, writing news articles requires not only a grasp of the 5W+1H elements, but also the ability to communicate, collaborate and provide feedback. This study aims to develop a journalism learning model focused on interpersonal intelligence to enhance the news writing skills of students at the University of Muhammadiyah North Sumatra. The study employed a research and development approach with a sample of 25 students. Data were collected through interviews, content expert validation, instructional expert validation, pre-tests and post-tests, and a student feedback questionnaire. Data analysis was conducted using both quantitative and qualitative descriptive methods. The research findings indicate that the model developed is highly valid, with a validation rate of 90% among subject matter experts and 90% among learning experts. The model was also effective in improving news writing skills, as demonstrated by the increase in the average pre-test score from 64.5 to 83.8 in the post-test. Furthermore, student feedback on the model was overwhelmingly positive, with 91.65% of respondents expressing approval. The novelty of this research lies in the integration of journalism training with interpersonal skills through discussion, collaboration, presentations and feedback within a systematic, collaborative and contextual model of news writing.